Cape Verde Investment Climate Assessment - World Bank (Washington, DC, 2013)
Cape Verde is a small country with a population of about 472,000 people spread over nine islands in a ten-island archipelago. It is more developed that most other countries in Sub-Saharan Africa. Its per capita Gross Domestic Product (GDP) per capita is US$5,715 in purchasing power parity (PPP) adjusted terms in 2004. The economy is dominated by the service sector, which accounted for about 75.5 percent of GDP in 2005. As a small island economy, Cape Verde is heavily dependent upon external economies. Remittances and foreign aid are important sources of capital and the economy is heavily dependent upon imports for much of its consumption and investment. Recent growth in the tourism sector has further increased Cape Verde's integration into the world economy. The main sources of information for the Investment Climate Assessment (ICA) are two surveys carried out in Cape Verde in March and April 2006. Both surveys were conducted in two locations, Praia and Mindelo. The first survey, the Investment Climate Survey (ICS), covered formal enterprises with over five employees in manufacturing, retail trade, construction, and other services. Firms were randomly selected from lists provided by the National Institute of Statistics (INE). The second survey, the Microenterprise Investment Climate Survey (MICS), covered Microenterprises in the same sectors. Firms in this sample were selected randomly in prescribed areas of the cities. This approach means that the survey will cover both registered and unregistered microenterprises. Because the two surveys were sampled using different methodologies and because there is no way to weight the firms in the two samples they are not pooled in the analysis.